Motivation and impact of international integration on science and technology: From theoretical view - Hoa, Trieu Bao (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Science and technology (S&T) international integration has become a natural trend and causes impacts to almost all the S&T sectors of all countries. All the countries have gained experience in adjustment and re-organization of their own activities to pay more attentions to implementation capacities and quality of research products in compliance with international standards. Namely, they focus priorities on links between enterprises and S&T organizations, domestic activities and international cooperation, training and recruitment of high quality human resources (including foreign ones), in order to benefit in maximum development opportunities and to become part of global S&T development. In this process, there are some nations which managed to make in-time adjustment and to capture opportunities offered from S&T international integration and, by this way, to enhance S&T forces to achieve the objectives of national development. But there also exist nations which could not capture momentum for adjustment of their systems and then could not face challenges of being left behind. These countries cannot promote values of S&T for national economy and contributions to the world’s S&T knowledge. In this paper, on basis of precious theoretical studies of many researchers, the author gives a system of visions to main driving forces which push up the S&T international integration process and cause impacts to the national S&T system. Some points are also suggested to present views to Vietnam international integration process. Code: 15030103